2017
DOI: 10.4172/pharmaceutical-sciences.1000202
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Species, Geographic Location, Seasonal Variation and Extraction Method on the Fucoidan Yield of the Brown Seaweeds of Gulf of Mannar, India

Abstract: Rani, et al.: Extraction Method on the Yield of Brown SeaweedsBrown seaweeds such as Sargassum wightii, S. oligocystum, Padina tetrastromatica and Turbinaria ornata were collected from two locations, Valinokkam and Hare Island in Gulf of Mannar, South East coast of India, to extract fucoidan and to analyse its variation in the yield for a period from July 2012 to January 2013. Water and acid extraction methods were followed to extract fucoidan. Water extraction yielded much higher fucoidan (9.46±0.18) than aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 27 publications
0
17
4
1
Order By: Relevance
“…The isolation yield was the highest in the red alga Grateloupia flilicina (28.5%, dry), and the others ranged from 2.8 to 5.7% (dry). Although there was no information for the isolation yields of the four commercial fucoidans (F85, F95, M85, and U95) used in this study, it has been reported that fucoidans were yielded in the rages of 3.9 to 9.5% from different brown algae [ 16 ]. In general, the cell walls of brown algae are composed of celluloses, alginates, and fucoidans in an average weight ratio of 1:3:1 (in the order mentioned) [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The isolation yield was the highest in the red alga Grateloupia flilicina (28.5%, dry), and the others ranged from 2.8 to 5.7% (dry). Although there was no information for the isolation yields of the four commercial fucoidans (F85, F95, M85, and U95) used in this study, it has been reported that fucoidans were yielded in the rages of 3.9 to 9.5% from different brown algae [ 16 ]. In general, the cell walls of brown algae are composed of celluloses, alginates, and fucoidans in an average weight ratio of 1:3:1 (in the order mentioned) [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are a number of commonly used methods to extract fucoidan, including water extraction, acid extraction, microwave-assisted extraction, ultrasonication extraction, and enzyme-assisted extraction [ 13 ]. There are reports that the yield of fucoidan varies with different extraction methods [ 14 ]. The extraction methods of fucoidan are briefly summarized in Table 1 .…”
Section: The Extraction Of Fucoidan From U Pinnatifida mentioning
confidence: 99%
“…Igarashi et al hydrolyzed the sporophyll of Japanese wakame, and the resulting infrared spectrum showed a band at 829 cm −1 and it was found that the bending vibration of C–O–S appeared at the C-2 position [ 15 ]. There are two other studies show that the bending vibration of C–O–S is present at different carbon locations, thereby indicating that sulfate is a characteristic group of the structure of fucoidan [ 12 , 14 ].…”
Section: The Structure and Function Of Fucoidan From U mentioning
confidence: 99%
“…Fucoidan content from seaweeds could vary from species to species, extraction method, geographical location, and seasonal variation (Rani et al 2017). Aside from species variety, the extraction method used by Jeon et al (2012) was not specific for fucoidan which could result to other compounds, such as alginic acid, to be included and affect the yield.…”
Section: Resultsmentioning
confidence: 99%